2017
DOI: 10.1007/s00134-017-4882-1
|View full text |Cite
|
Sign up to set email alerts
|

Focus on ECMO and ECCO2R in ARDS patients

Abstract: The technical aspects of veno-venous extracorporeal membrane oxygenation (vv-ECMO) are still improving, permitting the treatment of ARDS patients with very severe hypoxaemia. A recent German survey showed that the incidence of vv-ECMO in the population increased from 1.0:100,000 inhabitants/year in 2007 to a maximum of 3.0:100,000 in 2012, and then stabilised at 2.4:100,000 in 2014 [1]. The in-hospital mortality slightly decreased over time but remained high, at 58.1% in 2014. This real-life mortality rates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The calculus of the individualized DP allows us to determine the maximum DP that would deliver the maximum TV to be applied without worsening the established lung injury. Another benefit is that we would always know the top of DP to apply, and in case a patient would need higher levels of DP to maintain oxygenation or to maintain PaCO 2 in a reasonable range, perhaps other therapies could be considered (ECMO, ECCO 2 R), as recent studies suggest [ 17 , 18 ], to avoid severe hypercarbia while applying individualized protective ventilation according to the daily physical properties of the lung, but this should a matter of future studies. In addition, given that during ARDS, the lung may evolve from an inflammatory phenotype to a fibrotic form (especially in SARS-CoV-2 ARDS [19] ), daily analysis of the individualized DP and elastic limit may characterize the lung phenotype, providing knowledge of the evolutive tendency of the lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…The calculus of the individualized DP allows us to determine the maximum DP that would deliver the maximum TV to be applied without worsening the established lung injury. Another benefit is that we would always know the top of DP to apply, and in case a patient would need higher levels of DP to maintain oxygenation or to maintain PaCO 2 in a reasonable range, perhaps other therapies could be considered (ECMO, ECCO 2 R), as recent studies suggest [ 17 , 18 ], to avoid severe hypercarbia while applying individualized protective ventilation according to the daily physical properties of the lung, but this should a matter of future studies. In addition, given that during ARDS, the lung may evolve from an inflammatory phenotype to a fibrotic form (especially in SARS-CoV-2 ARDS [19] ), daily analysis of the individualized DP and elastic limit may characterize the lung phenotype, providing knowledge of the evolutive tendency of the lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of ECCO 2 R is not related only to excess CO 2 removal but also to spare work of breathing in spontaneously breathing COPD patients, to diminish dynamic hyperinflation (which can lead to barotrauma and volutrauma) in IMV COPD patients, and to achieve ultraprotective mechanical ventilation in moderate ARDS patients while diminishing tidal volume to 3-4 mL/kg predicted body weight, diminishing respiratory rate, and increasing positive end-expiratory pressure. The previous studies indicated that ECCO 2 R could significantly reduce carbon dioxide partial pressure (PaCO 2 ) in all treated patients than baseline values, including uncontrolled case series or case reports [1,[18][19][20][21][22][23][24][25][26][27][28]. It has been suggested that ECCO 2 R can avoid the need for IMV in 90% of the patients [29].…”
Section: Introductionmentioning
confidence: 99%
“…Extracorporeal membrane oxygenation (ECMO) originated from extracorporeal circulation technology, which provides days to weeks of life support for patients with respiratory failure and/or heart failure [ 3 ]. Early ECMO technology was mainly used as supportive care for acute respiratory distress syndrome (ARDS) in adults and for critical neonatal conditions [ 4 , 5 ]. With technological advancements, ECMO has become safer and more widely applied, with applications including perioperative bridging therapy in critical cardiothoracic surgical patients, supportive care for cardiogenic shock associated with cardiac emergencies (such as fulminant myocarditis and acute myocardial infarction) and auxiliary care for cardiopulmonary resuscitation [ 6–8 ].…”
Section: Introductionmentioning
confidence: 99%